TEENAGE EDUCATION AND CHARACTER BUILDING – A REPORT OF THE APPLICATION OF HYPNOPARENTING METHOD - Nurjanah Nurjanah; Muhammad Sulhan; Engliana Engliana (English Department - University of Sultan Ageng Tirtayasa, 2016)
Recently many adolescents have not received adequate character education either in their families or school environments and probably even both; it is to say that the result shows delinquent behaviors occurred among adolescents. In regards to these environments, there are other aspects may influence such behaviors, and to name a few, we have technology in hand. Technology and the Internet give us access to sufficient information – due to its nature is accessible to many - both advantages and disadvantages. These two-sided effects, however, are possible to control and minimize if proposed actions are taken to achieve the maximum benefits for building strong characters in adolescents. This writing reports the predetermined actions that took place in a community group (Rukun Warga or RW) in Cibereum, in the district of Cisarua, Bogor. It focuses on the members of Family Welfare Movement or Pemberdayaan dan Kesejahateraan Keluarga (PKK); the members are mothers with young children and adolescents of the community group. The program used in encouraging and raising awareness of the PKK members was a hypnoparenting method in their parenting style. At the end of the program, the PKK members could apply the skills learned throughout the program into their parenting practices. Keywords: character building; hypnoparenting; family; young adult education